Driving Factors for Rural Tourism-Driven Transformation in Traditional Chinese Villages: A Case Study of Chashan Village, Guangxi - ZOU, YU; Xu, Ming (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aims: This study employs a grounded theory approach to identify and analyze the key driving factors behind the successful transformation of Chashan Village into a rural tourism destination in Fuchuan County, Guangxi Zhuang Autonomous Region. The research aims to provide valuable insights into grassroots governance, community engagement, and cultural development as essential elements of successful rural transformation. Methodology: Employing a grounded theory approach, this study provides a deep, empirical investigation into the transformation process of Chashan Village, offering practical implications for rural revitalization strategies. It underscores the importance of inclusive community engagement, effective governance mechanisms, and cultural preservation in fostering sustainable rural development. Results: Our analysis reveals three distinct stages in the transformation process of Chashan Village: village regeneration (2014-2017), village development (2018-2021), and rural tourism formation (2022 to present). These stages reflect the village's transition from a hollow micro-economy to a vibrant rural tourism economy and then to a comprehensive village and town economy. Dynamic differences in driving factors are observed across the three transformation stages. During the village regeneration stage, elite governance, villager participation, and market resources are key drivers. In the village development stage, institutional governance, villager collaboration, and enhanced tourism experiences play pivotal roles. Finally, during the formation stage of villages and towns, community creation and public construction emerge as critical driving factors. Throughout Chashan Village's transformation and development journey, inclusive grassroots governance, active participation and cooperative behavior of villagers, and local construction of characteristic culture have played pivotal roles. These factors have not only promoted the village's in-depth development but also offered valuable lessons for rural revitalization efforts worldwide. Conclusions: The findings of this study contribute to a better understanding of the dynamics of village transformation and offer insights that can inform policy-making and community-led initiatives aimed at promoting rural revitalization globally.